2013
DOI: 10.1039/c3cp50330e
|View full text |Cite
|
Sign up to set email alerts
|

Dependence on the structure and surface polarity of ZnS photocatalytic activities of water splitting: first-principles calculations

Abstract: It has been reported that phase structure and surface polarity largely affect the photocatalytic efficiency of semiconductor nanostructures. To understand the chemical activity of ZnS at the electronic level, we investigate electron structures and carrier transportation ability for bulk intrinsic zinc blende (ZB) and wurtzite (WZ) ZnS, as well as the reaction pathway of hydrogen generation from water splitting on Zn-and S-terminated polar surfaces. The electron structure calculations prove that the WZ phase po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…The energy band gap was estimated to be 2.35 eV at the high symmetry G-point in the Brillouin zone for pure ZnS. Lashgari et al 59 reported that for 3D wurtzite-ZnS, the bandgap is 2.14 eV and 2D wurtzite-ZnS has a band gap of 2.77 eV at the PBE-GGA level of theory, also Meng et al 60 reported that bulk W-ZnS has a band gap of 2.09 eV, and our obtained optical gaps are comparable with these results. At the zero position in the band structures of the compounds in Fig.…”
Section: Raman Studymentioning
confidence: 96%
“…The energy band gap was estimated to be 2.35 eV at the high symmetry G-point in the Brillouin zone for pure ZnS. Lashgari et al 59 reported that for 3D wurtzite-ZnS, the bandgap is 2.14 eV and 2D wurtzite-ZnS has a band gap of 2.77 eV at the PBE-GGA level of theory, also Meng et al 60 reported that bulk W-ZnS has a band gap of 2.09 eV, and our obtained optical gaps are comparable with these results. At the zero position in the band structures of the compounds in Fig.…”
Section: Raman Studymentioning
confidence: 96%
“…18 In addition, it has also caused more attention in photocatalysis due to the fast generation of photogenerated electron-hole pairs 19 and more negative conduction band potential. 20,21 The theoretical efficiency of photocarrier generation of ZnS is even higher than that of TiO 2 . 22 For above reasons, ZnS is regarded as a highly active photocatalyst for hydrogen generation even without cocatalyst.…”
mentioning
confidence: 97%
“…In contrast, it is well known that pure DFT (LDA and GGA) underestimates the band gap of bulk ZnO and ZnS. [40][41][42][43][44] All the systems studied in this work have direct band gaps. In ZnO and ZnS, the top of the valence band is composed predominantly of anion p states, while the bottom of the conduction band is composed mostly of Zn 4s states.…”
Section: Electronic Propertiesmentioning
confidence: 66%